The Arrival of Fast Internet and Employment in Africa - Hjort, Jonas; Poulsen, Jonas (American Economic Review, 2019)
To show how fast Internet affects employment in Africa, we exploit the gradual arrival of submarine Internet cables on the coast and maps of the terrestrial cable network. Robust difference-in-differences estimates from 3 datasets, covering 12 countries, show large positive effects on employment rates—also for less educated worker groups—with little or no job displacement across space. The sample-wide impact is driven by increased employment in higher-skill occupations, but less-educated workers’ employment gain less so. Firm-level data available for some countries indicate that increased firm entry, productivity, and exporting contribute to higher net job creation. Average incomes rise. (JEL F14, J23, J24, J63, L86, O15, O33)